ENVIRONMENTAL FINANCIAL REPORTING PRACTICES AND QUOTED COMPANIES IN NIGERIA - Fakayode, Opeoluwa P.; Ola, Adeboboye Gbenga (Jurnal Ekonomi dan Bisnis Airlangga, 2025)
Introduction: The public's worries regarding company non-financial performance have increased due to environmental difficulties caused by industrial activities, and calls for environmental data disclosure have gotten stronger. The Global Reporting Initiative (GRI) and the International Organization for Standardization (ISO) have established standards for measuring firm environmental effectiveness and disclosing information within yearly reports; nevertheless, developing nations have not given these standards adequate consideration. The goal of this research was to evaluate the level of compliance with disclosure requirements among traded Nigerian companies. Methods: For the investigation, data that are both primary and secondary were used. To gather primary data, twenty percent (20%) of all listed Nigerian companies were selected at random and given a standardized questionnaire. From 2014 to 2023, secondary information was collected from the chosen companies' annual reports over a ten-year period. At the 5% level of significance, panel regression and ANOVA analysis were utilized to look into the relationships and effects between the study variables. Results: According to the results, a noteworthy distinction in the degree of corporate environmental disclosure was noted across a subset of traded businesses (p=0.224). 90% of respondents confirmed that the research area had corporate environmental disclosure practices in place.  Findings showed that OP, FL, SF, and environmental disclosure had a strong connection (R² = 0.6932). Conclusion and suggestion: According to the study's findings, environmental reporting by Nigerian listed corporations complies with ISO 14031 criteria. This study therefore recommended that policymakers should mandate disclosure of corporate environmental information.